Security Matters: Predictors of Self-Rated Prison Climate in Serbian Prisons - Milićević, Milena; Glomazić, Hajdana (NBP. Nauka, bezbednosti, policija, 2025)
Background: The prison climate significantly impacts prisoners’ quality of life and rehabilitation outcomes. This cross-sectional study aimed to identify which security-related dimensions predict prisoners’ evaluations of overall prison climate in the largest Serbian correctional institutions. Methods: We administered the Measuring the Quality of Prison Life (MQPL) survey to 543 (86% males) prisoners in four correctional facilities: Sremska Mitrovica, Niš, Požarevac–Zabela, and Požarevac. Most participants were aged 31–40, were serving sentences of 3 to 10 years under a closed regime, and nearly half had committed a violent offence or received disciplinary measures. We conducted hierarchical regression analyses to examine the predictive value of four MQPL dimensions (Policing and Security, Prisoner Safety, Prisoner Adaptation, and Drugs and Exploitation) on overall climate ratings. Results: Regime type significantly predicted overall climate ratings in Step 1 (β = .28), with semi-open regimes receiving more positive ratings. When MQPL subscales were added in Step 2, the explained variance increased from 8% to 28%. The predictive strength of regime type decreased (β = .12). Prisoner Safety (β = .28) and Policing and Security (β = .26) were the strongest predictors, while Prisoner Adaptation and Drugs and Exploitation were not significantly associated with overall ratings. Conclusions: While the structural regime type is important, prisoners’ evaluations of life in custody are primarily influenced by their perceptions of safety and adequate staff supervision. Improving institutional safety through fair and consistent supervision may have a greater impact on prison climate than regime classification alone. Keywords: prison climate, prison security, prisoner safety, staff supervision.
Keywords: prison climate; prison security; prison safety; staff supervision